Aprendizagem docente: desenvolvimento profissional de professores de classes rurais multisseriadas - Rabaiolli, Greice Ozelame (2010)
In this research, which falls in line search "training, knowledge and professional development" of the Post-Graduate Education of this University, we seek to discuss the issue of learning how to teach from the reality of teachers of multigrade rural schools. Thus, our objective was to understand the concepts and elements that make a teacher learning teacher multigrade rural classes in the early years of elementary teaching Putinga / RS, and the repercussions of these professional development of these subjects. The starting point of the methodological quality approach of sociocultural character, because we believe that with this approach, it is possible to take into account all the components of the research situation, interactions and meanings constructed. We evidenced thus the subject as social and historical construction, based on the Vygotskian conceptions of learning. In this sense, as an instrument to collect data for research, we used narrative interviews, oriented for guides-topic, because we believe that this way you can capture the meanings of teaching spaces in multigrade classes in rural areas. Thus, six teachers were collaborative research working in multigrade classes in the municipal Putinga, RS. From the analysis of the narratives of the teachers, it was possible to identify three categories that show the details of teacher learning in multigrade classes: the pedagogical organization, training processes and the knowledge teachers. The survey found also that all categories pointed out are linked to teacher's work as being this field of activity and source of production of teaching the teachers of multigrade classes collaborative areas. From the analysis of the narratives of the teachers could understand that the learning of teaching in these education is through the movement of breeding, when the teachers show only repeat practice, without thinking about them, but also by movements of creation, when recognized through reflection about their theoretical and methodological conceptions, the teachers seek to build a difference in you and your staff do. Therefore, the professional development of teachers is marked by the oscillation movement between breeding and reproduction, indicating that the teaching learning happens in the relationship between daily activities and relationships that the teachers are seeking to establish with their peers.